Back Cover: Ternary Organic Solar Cells with Reduced Graphene Oxide–Sb2S3 Hybrid Nanosheets as the Cascade Material (ChemNanoMat 5/2015). Issue 5 (31st August 2015) - Balis, Nikolaos; Konios, Dimitrios; Stratakis, Emmanuel; Kymakis, Emmanuel
Abstract : The Back Cover illustrates the use of reduced graphene oxide‐antimony sulfide (rGO‐Sb2 S3 ) hybrid nanosheets as the cascade material in ternary organic solar cells. Their utilization in PCDTBT:PC71BM blend leads to power conversion efficiency of 6.81%; a value 23% higher than the efficiency of the binary devices. The results demonstrate that the exploitation of on‐demand functionalized graphene derivatives as electron cascade materials is a promising way towards improving the performance of organic photovoltaics. More details can be found in the Full Paper by E. Kymakis et al. onpage 346 in Issue 5, 2015 . (DOI:10.1002/cnma.201500044 ).